Impact of Isolated Tricuspid Valve Repair on Right Ventricular Remodelling in an Adult Congenital Heart Disease Population - Marsico, Roberto; Bruno, Vito Domenico; Chivasso, Pierpaolo; Baritussio, Anna; Rapetto, Filippo; Guida, Gustavo A.; Benedetto, Umberto; Caputo, Massimo (Frontiers in Cardiovascular Medicine, 2017)
Background Surgical repair of isolated congenital tricuspid valve (TV) disease is rare with no well-defined indication and outcomes. Moreover, the role of right ventricle (RV) in this context has not yet been investigated. Objectives We sought to assess the impact of congenital TV repair on cardiac remodelling and clinical–functional status and the importance of the RV function in an adult congenital heart disease (ACHD) population. Methods and results From January 2005 to December 2015, 304 patients underwent TV surgery in our centre. Of these, 27 (ACHD) patients had isolated TV repair. Patients were evaluated with preoperative and postoperative transthoracic echocardiogram. Survival rate has been investigated with a mean clinical follow-up (FU) of 3.7 ± 2.3 years, whereas the mean echocardiographic FU was 2.9 ± 1.8 years. The clinical and functional status of patients showed a statistically significant improvement after the surgical repair in terms of New York Heart Association class (66.7 vs 7.4%; p < 0.01), clinical signs of heart failure (29.6 vs 7.4%; p < 0.01), and left ventricular function (14.8 vs 7.4%; p < 0.01). The RV and right atrium diameter were significantly reduced after surgery (5.15 ± 1.21 vs 4.32 ± 1.16; p < 0.01) and (44.7 ± 16.7 vs 26.7 ± 9.2; p < 0.01), respectively. The degree of postoperative pulmonary hypertension was also significantly reduced (40.7 vs 7.4%; p < 0.01). The survival rate was 96.3% at 1 year and 93.7% at 5 years. One patient (3.7%) had early failure of the tricuspid repair requiring a reoperation. Conclusion Isolated TV repair for adult congenital disease significantly improved patients’ clinical and functional status and allowed right ventricular remodelling and functional improvement.